2020
DOI: 10.1038/s41598-019-57149-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genetic diagnosis of Japanese patients with severe proteinuria

Abstract: Numerous disease-causing gene mutations have been identified in proteinuric diseases, such as nephrotic syndrome and glomerulosclerosis. this report describes the results of comprehensive genetic diagnosis of Japanese patients with severe proteinuria. in addition, the report describes the clinical characteristics of patients with monogenic disease-causing mutations. We conducted comprehensive gene screening of patients who had either congenital nephrotic syndrome, infantile nephrotic syndrome, steroid-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 25 publications
3
71
1
Order By: Relevance
“…Another interesting finding in this study is the higher prevalence of mutations in COQ6, COQ8B and NUP107, which was consistent with our previous studies [26][27][28]. An increased prevalence of COQ8B mutations was also found in a Chinese study [5], while an increased prevalence of NUP107 mutations was found in a Japanese study [6].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Another interesting finding in this study is the higher prevalence of mutations in COQ6, COQ8B and NUP107, which was consistent with our previous studies [26][27][28]. An increased prevalence of COQ8B mutations was also found in a Chinese study [5], while an increased prevalence of NUP107 mutations was found in a Japanese study [6].…”
Section: Discussionsupporting
confidence: 92%
“…This study showed a higher mutation detection rate in patients who presented with proteinuria than in patients who presented with NS (57.0% versus 34.5%, p < 0.001). Similarly, in a Japanese study [6], the absence of edema was one of the risk factors for genetic mutations in pediatric patients with severe proteinuria. In this study, the mutation detection rate was higher in patients without steroid treatment than in patients with initial steroid non-responsiveness (63.9% versus 39.7%, p < 0.001).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, recent advances in next-generation sequencing (NGS) have provided a revolutionary new approach for genetic diagnosis in terms of cost and effectiveness by allowing a panel of candidate genes or whole genes to be sequenced simultaneously. Mutations have been detected in approximately 30% of childhood-onset SRNS cases, according to large-cohort studies using NGS (Table 1) [2][3][4][5][6][7]. Thus, clinicians must select the best diagnostic tool for patients with a suspected genetic disorder.…”
mentioning
confidence: 99%